Sex differences in the association of skin advanced glycation endproducts with knee osteoarthritis progression. Issue 1 (December 2017) - Eaton, Charles; Sayeed, Maria; Ameernaz, Syeda; Roberts, Mary; Maynard, John; Driban, Jeffrey; McAlindon, Timothy
Abstract Background The accumulation of advanced glycation endproducts in articular cartilage has been suggested as an etiologic factor in the development and progression of knee osteoarthritis (KOA). Methods We conducted a prospective cohort study of skin advanced glycation endproducts (sAGEs) measured non-invasively by skin intrinsic fluorescence and the relationship between sAGE KOA progression in 160 men and 287 women in a sub-cohort of the Osteoarthritis Initiative at a single site. KOA progression was measured by yearly changes in Osteoarthritis Research Society International (OARSI)-defined joint space narrowing (JSN) and by yearly changes in joint space width (JSW) from baseline to 48 months. Sex-stratified repeated measures, mixed models to account for correlation between the knees within persons and adjusted for age, body mass index (BMI), Kellgren-Lawrence (KL) grade, beam angle and rim-to-rim distance were utilized. Results Increasing tertiles of sAGE measured at 36 months were associated with greater JSN over 4 years in men but not in women. The percentage of knees with JSN at 48 months, by tertiles of sAGE, were 7.0%, 16.0% and 17.7% in men (p for linear trend = 0.03) and 11.4%, 14.4% and 8.4% in women (p for linear trend = 0.33). Using change in JSW as the outcome, a similar trend was found in men but it was not statistically significant in fully adjusted models and no association was found in women. Conclusion This study provides preliminary evidence that sAGEs independent of age and BMI, are associated with knee JSN in men but not in women.